Effectiveness of Combination Antihypertensive Therapy for Controlling Blood Pressure in the Elderly - Taufiqurrahman, Abdullah; Alexander, Elijah (Lembaga Publikasi Ilmiah Nusantara, 2025)
Background: Hypertension is a prevalent condition among the elderly and a major risk factor for cardiovascular morbidity and mortality. Monotherapy often fails to achieve optimal blood pressure (BP) control in this population due to age-related physiological changes and comorbidities. Objective: This study aims to evaluate the effectiveness of combination antihypertensive therapy in achieving blood pressure control among elderly patients. Methods: A retrospective cohort study was conducted involving elderly patients (≥65 years) diagnosed with hypertension and receiving combination antihypertensive therapy. Blood pressure measurements were assessed at baseline and after 3 months of treatment. The primary outcome was the proportion of patients achieving target BP (<140/90 mmHg). Secondary outcomes included changes in systolic and diastolic BP and incidence of adverse effects. Results: Among 210 participants, 72.4% achieved target BP after 3 months of combination therapy. The mean reduction in systolic and diastolic BP was 18.6 ± 6.2 mmHg and 9.3 ± 3.8 mmHg, respectively. Combination therapy was generally well tolerated, with minimal adverse events reported. Conclusion: Combination antihypertensive therapy is effective and well tolerated in controlling blood pressure among the elderly. Its use should be considered in patients who do not achieve target BP with monotherapy, with close monitoring for potential side effects.